Seizures in Children with HIV infection in South Africa: A retrospective case control study. (February 2019) - Burman, R.J.; Wilmshurst, J.M.; Gebauer, S.; Weise, L.; Walker, K.G.; Donald, K.A.
Highlights: Neuroinfections and cerebrovascular accidents increase the risk of seizures in HIV-infected children. Neuroinfections and cerebrovascular accidents increase seizure-risk. Children with poorly controlled epilepsy are more likely to be receiving Efavirenz. Children presenting with seizures in this cohort were at increased risk of epilepsy. Abstract: Purpose: Data relating to the role that Human immunodeficiency virus (HIV) contributes towards seizures in HIV-infected children is limited. The management of seizures in this group is complex due to potential interactions between antiseizure medication and antiretroviral therapies. This study explores the seizure semiology and course of a population of affected children based on questions raised from a previous epidemiological study. Methods: A retrospective case-control study of all patients presenting to an HIV neurology clinic between 2008–2015 was conducted. A multinomial logistic regression model was used to identify risk factors for seizure occurrence in HIV-infected children, as well as factors associated with seizure control. Results: Of 227 HIV-infected children ( median 82 months, interquartile range 41–109), 52 (23%) reported a past or present history of seizures. Prior bacterial meningitis ( p = 0.03, OR 12.5, 95% CI 1.2–136.1), cerebrovascular accident (CVA, p = 0. 005, OR 8.1, 95% CI 1.9–34.9) and or tuberculous meningitis (TBM, p = 0.0004) was associated with an increased risk of seizures in HIV-infected children. Generalised tonic-clonic seizures were the predominant seizure type (64%) with the majority caused by an infectious aetiology (62%). Thirty-two (62%) of these patients had epilepsy in-line with the latest diagnostic criteria. HIV-infected children with epilepsy who were treated with efavirenz were more likely to have poor seizure control ( OR 23.1 95% CI 3.4–159.6, p = 0.0001). Conclusions: This study provides new data highlighting the complex clinical presentation and management challenges of HIV-infected children with seizures.